Percutaneous-endoscopic rendezvous procedure for the management of bile duct injuries after cholecystectomy: short- and long-term outcomes - Schreuder, Anne Marthe; Booij, Klaske A. C.; de Reuver, Philip R.; van Delden, Otto M.; van Lienden, Krijn P.; Besselink, Marc G.; Busch, Olivier R.; Gouma, Dirk J.; Rauws, Erik A. J.; van Gulik, Thomas M. (Endoscopy, 2018)
Background Bile duct injury (BDI) remains a daunting complication of laparoscopic cholecystectomy. In patients with complex BDI, a percutaneous-endoscopic rendezvous procedure may be required to establish bile duct continuity. The aim of this study was to assess short- and long-term outcomes of the rendezvous procedure. Methods All consecutive patients with BDI referred to our tertiary referral center between 1995 and 2016 were analyzed. A rendezvous procedure was performed when endoscopic or radiologic intervention failed, and when deemed feasible by a dedicated multidisciplinary team including hepatopancreaticobiliary surgeons, gastrointestinal endoscopists, and interventional radiologists. Classification of BDI, technical success of the rendezvous procedure, procedure-related adverse events, and outcomes were assessed. Results Among a total of 812 patients, rendezvous was performed in 47 (6 %), 31 (66 %) of whom were diagnosed with complete transection of the bile duct (Amsterdam type D/Strasberg type E injury). The primary success rate of rendezvous was 94 % (44 /47 patients). Overall morbidity was 18 % (10 /55 procedures). No life-threatening adverse events or 90-day mortality occurred. After a median follow-up of 40 months (interquartile range 23 – 54 months), rendezvous was the final successful treatment in 26 /47 patients (55 %). In 14 /47 patients (30 %), rendezvous acted as a bridge to surgery, with hepaticojejunostomy being chosen either primarily or secondarily to treat refractory or relapsing stenosis. Conclusions In experienced hands, rendezvous was a safe procedure, with a long-term success rate of 55 %. When endoscopic or transhepatic interventions fail to restore bile duct continuity in patients with BDI, rendezvous should be considered, either as definitive treatment or as a bridge to elective surgery.